HYGIENIC ASSESSMENT OF THE ACTUAL NUTRITION OF WOMEN IN THE CLIMACTERIC PERIOD (Western European Journal of Medicine and Medical Science, 2026)
Nutrition is one of the key factors in maintaining a normal physiological state and work capacity at any age. A balanced diet appropriate to age has a positive effect on the development of aging processes in the body and on the nature of changes occurring in its various systems. Rational nutrition is an essential component of a healthy lifestyle, as well as prevention and treatment of most non-communicable diseases. Nutrition serves as a means of normalizing the body’s condition and maintaining high performance. The main elements of rational nutrition include compliance with physiological needs in quantitative and qualitative terms, balance, and an appropriate dietary regimen. A balanced diet is defined as nutrition that ensures optimal proportions of nutrients and biologically active substances capable of exerting their maximum beneficial biological effect in the body. The principles of balance between proteins, fats, and carbohydrates have been studied and developed to the greatest extent